On the ionospheric response in the Taiwan region to Typhoon Meranti in September 2016 - Peng Chen; Mingzhu Xiong; Yibin Yao; Hao Chen; Fucai Tang; Liangcai Qiu; Yuchen Zhang (Geodesy and Geodynamics)
Previous studies have revealed that typhoons can affect the ionosphere. This paper uses GNSS observations provided by GNSS tracking stations of Taiwan region, ERA5 gravity wave dissipation products, and Himawari-8 band 07 brightness temperature observation data to analyze the impact of Typhoon Meranti on Taiwan region's ionosphere from September 13 to 15, 2016. In addition to the daily effects of traveling ionospheric disturbances (TIDs), TIDs of various intensities caused by Meranti-induced gravity waves were observed during this period, which is inseparable from the state of the typhoon and the topographic features during its progress. The ionospheric disturbance caused by the edge of a typhoon is usually larger than that at the typhoon eye. When the typhoon approached Taiwan region with high intensity on September 14, it was observed that the gravity waves caused by the typhoon had a wavelength of about 174–293 km, a period of 13.5–23.5 min, and a propagation speed of 142–302 m/s. When the vortex structure of a typhoon interacts with complex surfaces such as mountains, it is easier to excite more medium-scale gravity waves. The origin that excites gravity waves and causes ionospheric anomalies is different from the location of the typhoon eye and changes over time. The gravity waves caused by the typhoon lasted for three days in the central mountains of Taiwan region. Still, background wind conditions restricted the propagation of gravity waves from the mesosphere to the thermosphere and led to TID predominantly concentrated between 06:00 and 13:00 UT each day.